ETHNOMATHEMATICS IN STRUCTURE AND CARVING PATTERNS OF TORAJAN TRADITIONAL HOUSE BUILDING - Lidia Widia Sari (Universitas negeri Yogyakarta, 2023)
Toraja is one of the tribes in South Sulawesi, precisely in Tana Toraja. The Tana Toraja people are very famous for their strong cultural customs; there are so many spiritual activities, a series of traditional ceremonies, and cultures that are still very well preserved among the local community. Tongkonan is a Torajan traditional house building that is very popular and always attracts attention, including people from outside Tana Toraja, because the shapes and motifs of the carvings are unique; the shapes and motifs of these carvings cannot be separated from mathematical elements. This study is aimed at identifying Â the ethnomathematics contained in the carving patterns of the Tongkonan traditional house building. The research was qualitative with a descriptive method. The data collection technique used was a literature study. Results indicate that ethnomathematics in the structure of carving patterns on the Torajan traditional houses building can be integrated into various models of mathematics learning.